2022
DOI: 10.1158/1535-7163.mct-21-0358
|View full text |Cite
|
Sign up to set email alerts
|

Abdominopelvic FLASH Irradiation Improves PD-1 Immune Checkpoint Inhibition in Preclinical Models of Ovarian Cancer

Abstract: Treatment of advanced ovarian cancer using PD-1/PD-L1 immune checkpoint blockade shows promise; however, current clinical trials are limited by modest response rates. Radiotherapy has been shown to synergize with PD-1/PD-L1 blockade in some cancers but has not been utilized in advanced ovarian cancer due to toxicity associated with conventional abdominopelvic irradiation. Ultrahigh-dose rate (FLASH) irradiation has emerged as a strategy to reduce radiation-induced toxicity, however, the immunomodulatory proper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 37 publications
0
22
0
Order By: Relevance
“…Recent studies have indicated that FLASH-RT and CONV-RT might prime different immune responses in tumors, and better tumor control efficiency might be achieved due to increased recruitment of T lymphocytes. This has promoted research interest in combining FLASH-RT with immunotherapy to further enhance the therapeutic efficiency [17] . To further investigate the immunomodulation of FLASH-RT or CONV-RT, flow cytometry and IHC staining were performed to determine the immune response in tumor samples.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Recent studies have indicated that FLASH-RT and CONV-RT might prime different immune responses in tumors, and better tumor control efficiency might be achieved due to increased recruitment of T lymphocytes. This has promoted research interest in combining FLASH-RT with immunotherapy to further enhance the therapeutic efficiency [17] . To further investigate the immunomodulation of FLASH-RT or CONV-RT, flow cytometry and IHC staining were performed to determine the immune response in tumor samples.…”
Section: Resultsmentioning
confidence: 99%
“…However, regulatory T cells (T reg ), an important subset of CD4 + T cells, have immunosuppressive effects in tumors [30] , T reg can evade tumor-specific immune responses [31] . Eggold et al [17] reported that both electron CONV-RT and FLASH-RT could reduce regulatory T cells and increase cytolytic CD8 + T cells in the ovarian cancer TME 17 days PI, and that CD8 + T cell infiltration could be enhanced by a combination of αPD-1 treatment 12 or 17 days PI. In our study, CD8 + T cell infiltration was significantly increased in Py8119 xenograft tumor 2 weeks after both FLASH-RT and CONV-RT.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations